Heat Shock Tolerance in Deschampsia antarctica Desv. Cultivated in vitro Is Mediated by Enzymatic and Non-enzymatic Antioxidants - Cortés-Antiquera, Rodrigo; Pizarro, Marisol; Contreras, Rodrigo A.; Köhler, Hans; Zúñiga, Gustavo E. (Frontiers in Plant Science, 2021)
Deschampsia antarctica Desv, is the most successful colonizing species of a cold continent. In recent years due to climate change, the frequency of heat waves has increased in Antarctica, registering anomalous high temperatures during the summer of 2020. However, the populations of D. antarctica are responding positively to these events, increasing in number and size throughout the Antarctic Peninsula. In this work, the physiological and biochemical responses of D. antarctica plants grown in vitro (15 ± 1°C) and plants subjected to two heat shock treatments (23 and 35°C) were evaluated. The results obtained show that D. antarctica grown in vitro is capable of tolerating heat shock treatments; without showing visible damage to its morphology, or changes in its oxidative state and photosynthetic performance. These tolerance responses are primarily mediated by the efficient role of enzymatic and non-enzymatic antioxidant systems that maintain redox balance at higher temperatures. It is postulated that these mechanisms also operate in plants under natural conditions when exposed to environmental stresses.